MODELLING DSB REPAIR KINETICS FOR DNA DAMAGE INDUCED BY PROTON AND CARBON IONS. Issue 1 (21st January 2019) - Taleei, Reza
Abstract: Proton and carbon therapy are the main choices of particle therapy for cancer treatment. Particle dose distribution is superior to conventional photon therapy dose distribution due to Bragg peak. However, the basic biology of cellular damage and cell death is not well understood. The aim of this work is to present a mechanistic model of double strand break (DSB) repair that predicts the repair kinetics of damage induced by particles employed in cancer therapy. Monte Carlo Track Damage Simulation (MCDS) was employed to model DNA damage. The frequency of DSB and SSB was computed for proton and carbon ions. DSBs were subjected to repair model to calculate the repair kinetics. Two distinct DSB repair models dependent on the cell cycle were proposed. The DSB repair model contains non-homologous end joining (NHEJ), homologous recombination (HR) and back up non-homologous end joining (B-NHEJ) repair processes. The DSB complexity results in the switch in the repair pathway from NHEJ to a slower process that starts with DSB end resection. DSB end resection in early S and G1 phases of the cell cycle enhances the B-NHEJ repair pathway, while in late S and G2 phases of the cell cycle promotes HR repair pathway. The repair model was transformed to a set of nonlinear differential equations. The model calculates the overall repair kinetics and protein temporal repair activity at the site of damage. The damage and repair model provides a detailed mechanistic understanding of all processes that are involved in the damage induction and repair. The number of DSB and their complexity increase as the particle energy decreases due to the proximity of particle interactions in water. The repair kinetics show a biphasic behaviour that is due to the NHEJ fast repair of simple type DSB and HR slow repair of complex type DSB.